Rhizosediments of Salicornia tegetaria Indicate Metal Contamination in the Intertidal Estuary Zone - Nel, Marelé A.; Rubidge, Gletwyn; Adams, Janine B.; Human, Lucienne R. D. (Frontiers in Environmental Science, 2020)
Metal pollution is a well-known anthropogenic impact of highly developed estuaries, with dire consequences to the ecosystem. This study investigated the metal concentrations (Al, Cr, Cu, Fe, Mn, Ni, Pb, Zn) in the sediment colonised by Salicornia tegetaria, a dominant salt marsh plant in the lower intertidal zone of the Swartkops Estuary. The samples were collected at five sites along the banks of the middle and lower reaches of the estuary, and analysed using an Inductively Coupled Plasma - Optical Emission Spectrometer. Metal contamination was determined using established normalised baseline models. It was found that all the sites contained metal enrichment, with the estuary mouth experiencing the least enrichment. Salicornia tegetaria holds a substantial amount of anomalous metals within its rhizosediment — providing a valuable ecosystem service to a highly developed Swartkops Estuary.